The Northern Uganda Social Action Fund : Community Reconciliation and Conflict Management Empower Communities in a Post-Conflict Setting - World Bank (Washington, DC, 2012)
The five year Northern Uganda Social Action Fund (NUSAF), being implemented since 2003 is meant to assist government in its efforts to tackle poverty and bring about development that utilizes and builds on community value systems As part of the broader efforts to reconstruct Northern Uganda, NUSAF, as a project, and through direct grants to communities, is intended to: overcome underdevelopment through community action, leadership development, resource mobilization, strengthening the ongoing reconciliation processes in the region, and make it possible for communities to articulate and prioritize their specific needs and manage processes and outcomes, there by enhancing good governance for peace and development.